Climate exposure, vulnerability and environmental reliance: a cross-section analysis of structural and stochastic poverty - Angelsen, A.; Dokken, T. (Cambridge University Press, 2018)
We analyze links between exposure to climate extremes and shocks, vulnerability and coping strategies, environmental reliance and poverty among 7,300 households in forest adjacent communities in 24 developing countries. We combine observed income with predicted income to create four categories of households:income & asset poor(structurally poor),income rich & asset poor(stochastically non-poor),income poor & asset rich(stochastically poor) andincome & asset rich(structurally non-poor), and assess exposure and vulnerability across these groups. The income poor are more exposed to extreme climate conditions. They tend to live in dryer (and hotter) villages in the dry forest zones, in wetter villages in the wet zones, and experience larger rainfall fluctuations. Among the income-generating coping strategies, extracting more environmental resources ranks second to seeking wage labor. The poorest in dry regions also experience the highest forest loss, undermining the opportunities to cope with future climate shocks.